Comparison of Some Methods for the Elderly Patient Telemonitoring System - Hendra Setiawan; Elvira Sukma Wahyuni (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
This paper analyzes some research results related to patient telemonitoring system. The main objective is to collect many useful information for telemonitoring implementation and its development in the future. Telemonitoring system is focused on fall detection that generally occur prior to critical condition. There are 14 research results that discussed in this paper which have been published from 2013 to 2017. Those researches are grouped into three types i.e. intrusive, non-intrusive and mixed. Analysis is done on aspects of the comfort, complexity, cost, accuracy, and coverage. Furthermore, based on those information, a study of application feasibility is done for elderly patients in Indonesia. The result shows that the non-intrusive method using the camera or access point are the most appropriate system for the elderly fall detection.